A comparative study in learning curves of laparoscopic lateral suspension vs. laparoscopic sacrocolpopexy: preliminary results - Malanowska-Jarema, Ewelina; Osnytska, Yana; Starczewski, Andrzej; Balzarro, Matteo; Rubilotta, Emanuele (Frontiers in Surgery, 2023)
Background Determination of the learning curve of new techniques is essential to improve safety and efficiency. Limited information is available regarding learning curves of different techniques in laparoscopic pelvic floor surgery. Objective The aim of this study was to compare the learning curve of two operative techniques, laparoscopic lateral suspension (LLS) and laparoscopic sacrocolpopexy (LSC). Material and methods We conducted a prospective study to assess the learning curve of LLS and LSC by implementing a structured urogynecologic surgical training program with the use of pelvic trainers for our urogynecology fellow. The fellow was an experienced urogynecologic surgeon, but was laparoscopic suturing and dissection naive at the beginning of the study. She was required to assist in 20 laparoscopic urogynecologic surgeries and undertake laparoscopic suturing and knot tying training with mesh positioning on a laparoscopic trainer for 4 h/week during the trial period. After the completion of this structured training program, the fellow performed LLS and LSC under the supervision of an experienced subspecialist as the primary surgeon. Linear regression analysis was used to compare the data of LLS and LSC learning curves. Subjective pre- and post-operative evaluation of pelvic organ prolapse (POP) and pelvic floor disorders was undertaken preoperatively and 12 months postoperatively using the PFDI-20-Quality of Life validated questionnaire. Follow-up was scheduled 12 months after the surgery and performed by a skilled urogynecologist. Objective cure was defined as Pelvic Organ Prolapse-Qualification (POP-Q) stage <II in any compartment. Results The mean operative times of laparoscopic sacrocolpopexy and lateral suspension were 168.26 and 160.33 min, respectively. According to linear regression analysis after 43 procedures, the learning curve for laparoscopic lateral suspension was shorter than for laparoscopic sacrocolpopexy (OPTime 134.69 min). In both groups, there was a significant reduction in bothersome POP symptoms (p ≤ 0.005). Bladder injuries in two cases and lumbar pain in one case were recorded during the study. Overall objective success at 12 months was 90.7% for LSC and 89.1% for LLS. Conclusion Laparoscopic lateral suspension could be an alternative to laparoscopic sacrocolpopexy in the treatment of POP with its good objective and subjective outcomes. Lateral suspension has a shorter learning curve, and it is technically less demanding than LSC. Procedure-dedicated training can accelerate the move from a novice to a master laparoscopic surgeon.